Endodontic management in geriatric patient with medical compromised: Manajemen endodontik pada pasien geriatri disertai kompromis medis - Sakiyah Mustainah; Christine Anastasia Rovani (Makassar Dental Journal PDGI Makassar, 2022)
Endodontic treatment in geriatric patient with medical compromise is not a contraindication, but needs special treats, those are medical history, medical problems, psychological, age-related changes, changes in tooth structure, and tissue response. This ar-ticle is aimed to describe the role of management endodontic treatment in geriatric patient. A 62 years old male was diagnosed of tooth 16 as asymptomatic apical periodontitis. Radiographic examination shows widening of the periodontal ligament and periapical radiolucency. The patient has a history of hypertension and takes medication regularly. The endodontictreatment pro-cedure is preceded by IEC to the patient regarding the multivisit endodontic treatment by fulfilling the endodontic triad princi-ples. The treatment was conducted in the morning with short duration. Rubber dam was used in this treatment before rewalling and other procedures. Root canal preparation using rotary Protaper Next files on mesiobuccal up to X2 file (#25/06) and X3 file (#30/07) on mesiodistal and palatal canals. The root canals were irrigated using5.25% NaOCl and aquades. The root canal fil-ling technique was performed using a single cone technique, an epoxy resin sealer and gutta-percha materials. Theresult showed endodontic treatment multivisit in geriatric patient with compromise medis is succesfull. It was concluded that appropriate en-dodontic management in geriatric patient with medical compromise will support the success of the treatment.